Chemical profile from the head of Vespa velutina and V. crabro - Rodríguez-Flores, M. Shantal (2018)
Vespa velutina and V. crabro are eusocial insects in which chemical communication is decisive for social interactions. V. velutina was accidentally introduced in 2004 in France and subsequently in northern Spain in 2010. It is an invasive species that severely affects the beekeeping sector. The hornet autochthonous V. crabro with a similar ecological niche is captured in bait traps used to control V. velutina populations. Insect cuticle and head structures had an important role in chemical communication so that this research approaches for the first time chemical compounds extracted from the heads of V. velutina and V. crabro. Chemical compounds were profiled using GC/MS. The main compounds identified were carbohydrates, fatty acids, and hydrocarbons. The chemical profile of both species was compared and also an intrinsic differentiation was made between queens and workers in V. velutina. Chemometric techniques (PCA and LSD) were used to achieve this goal.